Influence of microscale environmental factors on perceived walk accessibility to metro stations. (February 2019) - Bivina, G.R.; Gupta, Akshay; Parida, Manoranjan
Highlights: Structural Equation models analyzed the influence of micro scale built environment variables on perceived walk accessibility. Four latent constructs such as Safety & Security, Comfort & Convenience, Mobility and Infrastructure and Traffic factors significantly affects walk accessibility The policies and design implications for improving walk accessibility to metro station are proposed. Abstract: Despite the successful implementation of metros in densely populated Indian cities, only scant attention has been paid by government officials, planners and researchers to improving pedestrian accessibility to metro stations. The present study attempts to explore the impact of various microscale built environmental factors on pedestrian satisfaction with regard to access to metro stations, gathering comprehension into design strategies and policy interventions that can improve pedestrian access. Personal interviews were conducted among metro users living in the vicinity of metro stations in Delhi, India. Information was collected on individual, household and trip characteristics and attitude of people on various environmental factors affecting pedestrian access to the metro. The database collected was analyzed by developing structural equation models. It has been found that four latent constructs affect the perception of pedestrian access to metro stations: safety and security; comfort and convenience; mobility and infrastructure, and traffic factors. Among all the latent constructs, safety and security is the most influential factor regarding pedestrian access, suggesting that it should be explicitly considered as the main factor for understanding the pedestrian access to metro stations. The findings of the study not only call on researchers to explore an inclusive set of environmental and psychological factors affecting pedestrian accessibility to metro stations, but also to understand various aspects of people's satisfaction in using pedestrian facilities, and in addition for the planners to endorse various design perspectives that will generate a more acceptable and satisfactory pedestrian environment around the metro stations.